One-Pot Synthesis of 5,6-Dihydro-4H-1,2-Oxazines by Cyclization of Ketoximes with Derivatives of Allylbenzene (JOURNAL OF ADVANCES IN CHEMISTRY, 2010)
A new series of 5,6-dihydro-4H-1,2-oxazines were synthesized via hetero Diels-Alder reaction ofÂ  Î±-nitrosolefins with derivatives of allylbenzene. Î±-Nitrosoolefins were generated from ketoximes by the action of chloramine-T and triethylamine.